Facies sedimentares e ambientes deposicionais da Formação Barbalha no vale do cariri, bacia do araripe, nordeste do Brasil - Chagas, Daniel Bezerra das [UNESP]; Assine, Mário Luís [UNESP]; Freitas, Francisco Idalécio de (My University, 2007)
The Aptian Barbalha Formation represents the first unit of the post-rift sequence of the Araripe Basin and crops out at the slopes of the Aranpe plateau in the eastern part ot Aranpe Basin. The unit has also been named Kio da Batateira Formation, but this name is here used in its original definition as Batateira Beds, an interval of great lateral continuity and characterized by the presence of bituminous shales of the Alagoas Stage (P-270 palynological biozone). This paper presents the results of a stratigraphic analysis carried out along the outcrop belt in order to establish the facies architecture and to interpret deposicional environments of the siliciclastic Barbalha Formation. Detailed stratigraphic vertical sections were measured and correlated. They allowed the recognition of two depositional sequences characterized by fining upward arrangement of facies, beginning with fluvial deposits and ending with lacustrine deposits at their tops. The end of the first cycle is represented by black shales and brecciated limestones of the Batateira Beds that record a geologic event of regional magnitude and serve as meaningful long-distance stratigraphic mark. The second deposicional sequence overlies disconformably the Batateira Beds and begins with clast-supported conglomerates, which are covered by a succession of fluvial sandstones and minor intervals of pelitic rocks. The sandstone content diminishes towards the top and the upper part of the unit is characterized by the presence of ostracode-rich green shales. The Barbalha Formation is conformably overlaid by Late Aptian lacustrine limestones belonging to the Crato Member of the Santana Formation.

A Formação Barbalha, de idade aptiana, constitui o registro sedimentar da parte inferior da seqüência pós-rifte da Bacia do Araripe. Neste trabalho são apresentados os resultados de análise estratigráfica realizada na faixa de afloramentos da unidade no Vale do Cariri, sul do Estado do Ceará, onde foram levantadas várias seções-colunares, descritas e analisadas as fácies e interpretadas as associações de fácies presentes. Foram caracterizadas duas seqüências deposicionais com padrão textural de granodecrescência ascendente, registro de dois ciclos estratigráficos de natureza sedimentar continental. A seqüência mais antiga é dominantemente constituída por fácies fluviais, sendo sua porção superior representada pelas Camadas Batateira, um intervalo de grande continuidade lateral, registro de evento geológico de magnitude regional, e marco estratigráfico muito útil para correlações e balizamento de seções estratigráficas na Bacia do Araripe. Nas Camadas Batateira predominam folhelhos pretos ricos em matéria orgânica, com conteúdo palinológico da biozona P-270 do Andar Alagoas. A segunda seqüência deposicional assenta-se em discordância erosiva sobre a primeira, estando presentes conglomerados na base de fácies fluviais. O topo da segunda seqüência é marcado pela presença de folhelhos verdes, que são sobrepostos concordantemente por folhelhos e calcários laminados neoaptianos do Membro Crato da Formação Santana.
Sedimentary facies and depositional environments of the Barbalha Formation, Araripe Basin, northeastern Brazil
Keywords: Araripe basin; Barbalha Formation; Batateira beds; Fining-upward sequences; Late Aptian; black shale; conglomerate; deposition; limestone; sandstone; sedimentary basin; shale; stratigraphy; Alagoas; Araripe Basin; Brazil; South America; Ostracoda